Innovative curing chamber for sustainable green geopolymer brick - Mohd Zulfahmi, Ibrahim (2013)
The aim of this study is to create a new technology to dry the brick that made from fly ash. This technology is simple, efficient, inexpensive and also using a green technology. The technology that I propose in this research is innovative chamber. This technology is based on direct solar heat type. This concept makes the solar heat distributed from above to below the chamber through the roof. The chamber is made using steel structure and has two sections. The wall of this chamber has three layers to make the chamber seal the heat inside the chamber much longer. The chamber temperature was observed under daytime and the temperature range in the chamber is between 30°C to 55°C. The fly ash brick specimen is designed and constructed to test the efficiency of the chamber. There are two mixtures of fly ash brick which is 90kg/m3 and 100kg/m3 of sodium silicate. For curing process, there are three different conditions namely, in the chamber, in the oven and at the ambient. The compressive test was conducted in 3,7,28 days. The result from compressive test shows that curing condition significantly affects the mechanical properties of fly ash brick.